2022
DOI: 10.3389/fneur.2022.802516
|View full text |Cite
|
Sign up to set email alerts
|

Instrumented Assessment of Motor Performance Fatigability During the 6-Min Walk Test in Mildly Affected People With Multiple Sclerosis

Abstract: There are conflicting results regarding the changes in spatio-temporal gait parameters during the 6-min walk test (6MWT) as indicators of gait-related motor performance fatigability (PF) in people with Multiple Sclerosis (pwMS). To further analyze if gait-related motor PF can be quantified using instrumented gait analysis during the 6MWT, we investigated: (i) whether gait parameters recorded during the first or second minute were more stable and thus the better baseline to assess motor PF and (ii) if the minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
1
4
1
Order By: Relevance
“…34 One may argue that the first minute of the 6MWT has more variability given the adaptation in the test and, therefore, is less stable compared to the second minute and may not be used to identify motor fatigability in pwMS. 44,58 Nevertheless, our results showed good to excellent reliability for gait characteristics in minute 1, which may address this issue raised elsewhere. Finally, we did not include all possible gait characteristics for all gait domains (eg, intra/inter-limb coordination or dynamic control asymmetry) or the calculation of the Lye in all possible planes (anteroposterior, medial-lateral, and vertical), which can give extra information on walking fatigability.…”
Section: Limitationssupporting
confidence: 66%
“…34 One may argue that the first minute of the 6MWT has more variability given the adaptation in the test and, therefore, is less stable compared to the second minute and may not be used to identify motor fatigability in pwMS. 44,58 Nevertheless, our results showed good to excellent reliability for gait characteristics in minute 1, which may address this issue raised elsewhere. Finally, we did not include all possible gait characteristics for all gait domains (eg, intra/inter-limb coordination or dynamic control asymmetry) or the calculation of the Lye in all possible planes (anteroposterior, medial-lateral, and vertical), which can give extra information on walking fatigability.…”
Section: Limitationssupporting
confidence: 66%
“…These findings are in line with previous studies describing that a decrease in walking speed is not adequate for describing walking fatigability in mildly disabled pwMS (EDSS 0-3.5). (Broscheid et al, 2022;Escudero-Uribe et al, 2019) Although increased gait variability is related to gait deterioration and self-reported fatigue in pwMS with mild disability, (Shema-Shiratzky et al, 2019;Zanotto et al, 2022) the increased RPE in our study was not accompanied by an increased gait variability. This is in line with the results from Crenshaw et al reporting no change in kinetic and kinematic variability before and after fatigue assessed with an increase in RPE.…”
Section: Discussioncontrasting
confidence: 40%
“…The increased RPE during the 6MWT is in line with other studies including pwMS. (Hadouiri et al, 2021;Broscheid et al, 2022) This increment is suggested to be clinically significant when compared to other patient populations. (Ries, 2005) Therefore, it can be concluded that the 6MWT induced perceived exertion.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies showed that persons with mild impairments (EDSS range 1-4) walk slower during the 6-minute walk test, compared to control subjects. This slower walking speed during the 6-minute walk test is accompanied by shorter step lengths and lower cadences in all levels of disability, compared to control subjects Notably, walking speed decreases with increasing disability 42,43 . As described above, gait impairments are also affected by impaired neural control which stipulates the difference from gait impairments in persons with RA.…”
Section: Gait In Persons With Ms and Ramentioning
confidence: 78%
“…The increased RPE during the 6MWT is in line with other studies including pwMS. 42,199 This increment is suggested to be clinically significant when compared to other patient populations. 200 Therefore, it can be concluded that the 6MWT induced perceived exertion.…”
Section: Discussionmentioning
confidence: 97%